Model Pembelajaran Montessori dalam Membangun Kedisiplinan Anak di TK Awliya Kota Cirebon - Muidatul Faziyah; Muqawim Muqawim (Institut Agama Islam Negeri Madura, 2020)
Discipline is very important to be developed early on, while the definition of discipline itself is giving an understanding to which children should be obeyed and which should be avoided. Discipline also teaches children about making mistakes will certainly contain a number of consequences, for this reason the function of punishment in children's education. Discipline is a behavioral value that can be done by force and can be done voluntarily. This Montessori-based learning model can build discipline starting from getting children to tidy up their former food, washing dishes, being able to take responsibility for the assignments given by their teacher, which has been applied in kindergarten Awliya, Cirebon. This research uses descriptive qualitative method that seeks to provide background, unique characteristics. The data obtained through interviews, observation and documentation. The results showed that children in the Awliya Kindergarten in Cirebon City could build their discipline through a Montessori-based learning model. This habit is a rare beginning in building discipline in early childhood.